2018
DOI: 10.1007/s10144-018-0612-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variability may not compensate for increasing climatic volatility

Abstract: The role of intraspeciic variability is being examined to improve predictions of responses to climate change or invasions and in research on diversity. Simultaneously, the probability and implications of increased high-frequency climate variability have been raised. An agent based model simulated two species on an environmental gradient representing an alpine treeline; a trend in its volatility was added. The species have diferent levels of variability, and each individual has further unique heterogeneity. Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Messer and Petrov 2013) variation. In general, such variation should improve the performance and adaptive potential of plants to environmental variation (see Malanson (2018) for a simulation study of the role of intraspecific variability and climatic volatility). Imbert and Ronce (2001) showed that heteromorphic Asteraceae increase the dispersal of their progeny under environmental stress by varying the relative proportion of wind- and animal-dispersed seed morphs.…”
Section: What Is the Consequence Of Rapid Change In Seed Dispersal Fomentioning
confidence: 99%
“…Messer and Petrov 2013) variation. In general, such variation should improve the performance and adaptive potential of plants to environmental variation (see Malanson (2018) for a simulation study of the role of intraspecific variability and climatic volatility). Imbert and Ronce (2001) showed that heteromorphic Asteraceae increase the dispersal of their progeny under environmental stress by varying the relative proportion of wind- and animal-dispersed seed morphs.…”
Section: What Is the Consequence Of Rapid Change In Seed Dispersal Fomentioning
confidence: 99%
“…For example, a global dataset would allow comparisons of multiple regions (e.g., Testolin et al, 2021), but further database developments are needed (e.g., to sPlot; Bruelheide et al, 2019) as are simulations with higher spatial and biological resolution. Better quantification of isolation, with recognition of past pathways as well as dispersal kernels, could define a gradient of isolation that could underlie differences in the processes determining plant community assembly (Saura et al, 2014), and the inclusion of more realistic response or fitness functions of species, with competition, facilitation, and intraspecific variation (e.g., Malanson, 2015Malanson, , 2018, would allow more rigorous tests of outcomes other than beta diversity.…”
Section: Discussionmentioning
confidence: 99%
“…We created virtual species with fitness representing geographic legacies or adaptation to climatic gradients, assuming that the former was useful for the purpose of comparison because a true null model was a weak strawman (substantiated preliminary analyses of a null model; cf. Malanson, 2018). We created a spatially explicit individual-based simulation with Monte Carlo reproduction, dispersal, and mortality in Netlogo (v6.1.1;Wilensky, 1999); Bauduin et al (2019) summarized the advantages of such simulations, which have a long history in alpine ecology (e.g., Humphries et al, 1996).…”
Section: Methodsmentioning
confidence: 99%